2007
DOI: 10.1369/jhc.7a7323.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Patterns of NDRG Family Proteins in the Central Nervous System

Abstract: S U M M A R Y The N-myc downstream-regulated gene (NDRG) family consists of four proteins: NDRG1, NDRG2, NDRG3, and NDRG4 in mammals. NDRG1 has been thoroughly studied as an intracellular protein associated with stress response, cell growth, and differentiation. A nonsense mutation in the NDRG1 gene causes hereditary motor and sensory neuropathy, Charcot-Marie-Tooth disease type 4D. We previously generated Ndrg1-deficient mice and found that they exhibited peripheral nerve degeneration caused by severe demyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 17 publications
(28 reference statements)
11
92
0
Order By: Relevance
“…NDRG4 expression was mainly observed in NeuN-positive cells but not in GFAP-positive cells, indicating that NDRG4 was specifically expressed in neurons. This was consistent with our previous finding that NDRG4 protein was expressed in neurons of the cerebral cortex and Purkinje cells of the cerebellum (17).…”
Section: Localization Of Ndrg4 In Mousesupporting
confidence: 94%
See 2 more Smart Citations
“…NDRG4 expression was mainly observed in NeuN-positive cells but not in GFAP-positive cells, indicating that NDRG4 was specifically expressed in neurons. This was consistent with our previous finding that NDRG4 protein was expressed in neurons of the cerebral cortex and Purkinje cells of the cerebellum (17).…”
Section: Localization Of Ndrg4 In Mousesupporting
confidence: 94%
“…Anti-NDRG2, anti-NDRG3, and anti-NDRG4 rabbit antisera were raised against the synthetic peptides Q 351 SSESGTLPSGPPGH 365 for mouse NDRG2 (17), F 343 SRSVTSNQSDGTQE 357 for mouse NDRG3 (17), and C-N 214 RPGTVPNAKTLR 226 -CONH 2 for mouse NDRG4, respectively, which were conjugated with keyhole limpet hemocyanin. Polyclonal antibodies in the antisera were purified by antigen-immobilized affinity column chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have shown that the level of hyperphosphorylated forms of NDRG2 protein is increased in the diencephalic samples from mice with increased homeostatic sleep need. NDRG2 is an astrocytic protein (29) of which the cellular function is poorly characterized. NDRG2 may be a substrate for a number of protein kinases, and our preliminary data indicate that the hyper-phosphorylated NDRG2 spots are recognized by antibodies against Akt substrates as well as by those against PKC substrates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein differential display was carried out using a 2D-DIGE system (GE Healthcare), and target protein spots were identified by nano-liquid chromatography-tandem mass spectrometry (nano-LC/MS/MS) operated by the UTSW Protein Chemistry Technology Center. Confirmation of 2D-DIGE results was performed by 1D Western blot using phosphorylated protein and total protein samples against anti-DNM1 (Abcam) and anti-NDRG2 antibodies (29). Values were then expressed relative to the ÎČ-tubulin.…”
Section: Methodsmentioning
confidence: 99%